Three treatises, in which the fundamental principle, doctrines, worship, ministry and discipline of the people called Quakers, are plainly declared - Penn, William; Barclay, Robert; Pike, Joseph; Adams, James ([Verlag nicht ermittelbar], 1783)
A brief account of the rise and progress of the people called Quakers. 7th ed. By William Penn.--The anarchy of the Ranters, and other libertines. By Robert Barclay.--An epistle to the National Meeting of Friends in Dublin, concerning good order and discipline in the church. Written by Joseph Pike.